The Arms Trade Treaty: U.S. Arms Sales to Taiwan and U.S.-China Relations - Ramadhani, Eryan (Global and Policy Journal of International Relations, 2013)
ABSTRACTThe dynamic of U.S.-China relations cannot be secluded from Taiwan-related issue. Falling into a treacherous category is the ceaseless U.S. arms sales to Taiwan under the scheme of Taiwan Resolution Act (TRA) that obligated the former to provide the latter with arms of defensive character, resulting in uneasiness among the leaders in Beijing. Congenial to its endeavor to cut out the knit-tight relations between the U.S. and Taiwan, China intends to exert the Arms Trade Treaty (ATT) as a means to condemn U.S. arms sales to a non-state actor carrying lethal weapon able to mar the existing status quo in the region. This paper aims to elucidate the positions of the U.S. and China on the ATT to which both states currently are not the parties. With emphasis on Taiwan, it is argued that both the U.S. and China will be persistent to uphold pragmatism, covering also the ATT, without seriously harming the strategic relations between the two.Keywords: ATT, U.S. arms sales to Taiwan, U.S.-China relationsDOI:https://doi.org/10.33005/jgp.v1i02.1996